The Synthesis of Modern Consumer Preferences with the Use of Social Networks in Supply Chain - Volkov, Daniil V.; Vinogradova, Marina V.; Kulyamina, Olga S. (International Journal of Supply Chain Management, 2018)
In modern realities, the main driving force in the formation of the sales market is marketing technologies. With the development of public information technologies in the face of social networks in supply chain, businesses have new levers of control of the target audience, which allows to synthesize consumer preferences. Social networks in supply chain provide a range of quality information that allows us to offer consumers the goods and services in which they are interested. The adaptation of the achievements of marketing technologies of the past years to the new semantic environment brings results that have a positive impact on economic growth. The study examines the classical marketing techniques in conjunction with the micro-segmentation of the audience of social networks in supply chain. Profiling of search engines is inherently associated with this, the most advanced method of product promotion.